2009 European Conference on Radiation and Its Effects on Components and Systems 2009
DOI: 10.1109/radecs.2009.5994577
|View full text |Cite
|
Sign up to set email alerts
|

MUSCA SEP<sup>3</sup> contributions to investigate the direct ionization proton upset in 65nm technology for space, atmospheric and ground applications

Abstract: This paper presents the investigation of upset induced by direct ionisation of proton in 65nm technology and evaluates the operational SER consequences in space, atmospheric and ground environments.Index Terms -direct ionization of proton, operational SER, nanometric technology, space -atmospheric -ground applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…As feature sizes scale down, charge collection at multiple nodes (i.e., charge sharing) due to a single particle hit result from the decrease in spacing dimensions between cells [4][5][6][7]. The sensitivity of the SEE is expected to increase and recent studies have demonstrated the occurrence of SEs due to protons [8,9] and muons [10] for advanced nano-scale electronics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As feature sizes scale down, charge collection at multiple nodes (i.e., charge sharing) due to a single particle hit result from the decrease in spacing dimensions between cells [4][5][6][7]. The sensitivity of the SEE is expected to increase and recent studies have demonstrated the occurrence of SEs due to protons [8,9] and muons [10] for advanced nano-scale electronics.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations were performed and validated in several scientific fields, such as operational calculations [23,24], nano-scale technologies (bulk, FDSOI [10] and FinFET [25]) and the design impact on SEE responses [26], transport/ collection models [27] and emerging problematic issues (direct ionizing protons [9] and muons). Significant works have additionally investigated the contribution of the radial ionization profile of SEE modeling [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…As feature sizes scales down, charge collection at multiple nodes (i.e., charge sharing) due to a single particle hit results from the decrease spacing dimensions between cells [12][13][14][15]. Then the sensitivity to SEE is expected to increase and recent studies have shown the occurrence of soft-errors due to protons [16,17] and to muons [18] for advanced nano-scales electronics. In order to know the muon contribution in soft-errors, the first requirement is to ensure a solid understanding of the muon radiation environment.…”
Section: Background and Contextmentioning
confidence: 99%
“…Initial information was presented by Heidel et al [6] and was expanded by Sierawski et al [2], Cannon et al [4], and Hubert et al [3]. A lot of this debate centered on whether experimenters had to use degraded beams of low-energy protons with significant straggle or, since primary particle direct ionization was the assumed mechanism, whether a surrogate beam of alpha particles or other low-linear energy transfer (LET) light ions could be utilized to simulate the low-energy protons' electronic LET and thus the correct proportion of SEUs with enough fidelity to make accurate event rate calculations.…”
Section: Introductionmentioning
confidence: 99%